2018
DOI: 10.1101/481416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ribozyme-Mediated, Multiplex CRISPR Gene Editing and CRISPRi in Plasmodium yoelii

Abstract: 1Functional characterization of genes in Plasmodium parasites often relies on genetic 2 manipulations to disrupt or modify a gene-of-interest. However, these approaches are limited by 3 the time required to generate transgenic parasites for P. falciparum and the availability of a 4 single drug selectable marker for P. yoelii. In both cases, there remains a risk of disrupting native 5 gene regulatory elements with the introduction of exogenous sequences. To address these 6 limitations, we have developed CRISPR-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Similarly, C-terminal tagging of the protein with a ligand-regulated Escherichia coli dihydrofolate reductase destabilization domain 39 for protein knockdown was unsuccessful. We therefore applied a genome editing-free method for gene down-regulation termed CRISPR interference (CRISPRi) 40 which has recently been adapted for Plasmodium 41,42 and is based on an enzymatically inactive (‘dead’) Cas9 protein (dCas9). In this method, the Cas9 protein is rendered inactive by two point mutations (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, C-terminal tagging of the protein with a ligand-regulated Escherichia coli dihydrofolate reductase destabilization domain 39 for protein knockdown was unsuccessful. We therefore applied a genome editing-free method for gene down-regulation termed CRISPR interference (CRISPRi) 40 which has recently been adapted for Plasmodium 41,42 and is based on an enzymatically inactive (‘dead’) Cas9 protein (dCas9). In this method, the Cas9 protein is rendered inactive by two point mutations (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As gene knockout was not possible, we used the recently developed CRISPRi system 4143 to demonstrate the role of PfMT-A70 in the m 6 A methylation pathway. Because P. falciparum lacks the RNA interference pathway, application of CRISPRi is an invaluable new genome editing-free technique for targeted gene knockdown and functional characterization of essential genes in the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Our collective experience to date indicates that homology regions of >250–1000 bp are sufficient (Figure 1b), a similar range also observed by Ribeiro et al . [32], with efficient editing of P. yoelii with homology arms as short 80–100 bp as reported by Walker and Lindner [23]. However, to date there have been no reports of success using the very short homology regions (<50 bp) that are effective in Toxoplasma [40, 41].…”
Section: Introductionmentioning
confidence: 97%
“…Further developments in P. yoelii have included the production of a male/female reporter line expressing sex-enriched fluorescent proteins, as well as a parasite line constitutively expressing SpCas9 that would reduce the size of plasmids required [21, 22]. Recently, Walker and Lindner have reported the use of RNA polymerase II promoters to transcribe a ribozyme–guide–ribozyme system (CRISPR-RGR) in P. yoelii that can achieve high editing efficiencies for gene deletions and tag insertions [23]. This work also demonstrated that the number of gRNAs used influences gene editing outcomes, where using one gRNA can result in parasites bearing either plasmid integration and locus replacement gene edits, while using two gRNAs produces parasites with only locus replacement events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation